Resilience and deterrence: exploring correspondence between the concepts - Wilkinson, Edith (Springer, 2020)
Classic theories of deterrence do not envisage the concepts of resilience and deterrence as even remotely connected. However, these two notions may not be poles apart and may, in fact, offer complementary perspectives in envisioning options for dealing with the security challenges of the twenty-first century. This chapter explores the correspondence between the two concepts. Firstly, it discusses definitions and key tenets of these concepts in relation to security. Then, it goes on to review what differentiates and what links these concepts in terms of the risk approach each presents; this includes an examination of rationality in deterrence and resilience frameworks as well as looking at the growing acknowledgement that their evolution is influenced by systems thinking. The chapter then considers in what way deterrence theory and the emerging resilience theory display areas of complementary and mismatch. This is achieved by examining how, on the one hand, both approaches may be able to support one another and, on the other hand, how the significance of change and transformation in both frameworks can provide pointers to where future thinking might lead.
Keywords: Deterrence; Resilience; Security; Risk